Oral shedding of human herpesviruses in patients undergoing radiotherapy/chemotherapy for head and neck squamous cell carcinoma is not affected by xerostomia - Michelle Palmieri; Mariana Ornaghi; Victor Adriano de Oliveira Martins; Luciana Correa; Thais Bianca Brandao; Ana Carolina do Prado Ribeiro; Laura Masami Sumita; Tania Regina Tozetto-Mendoza; Claudio Sergio Pannuti; Paulo Henrique Braz-Silva (Journal of Oral Microbiology, 2020)
Background: Xerostomia is a very relevant and frequent complication of radiotherapy, causing the irradiated oral mucosa to be affected by bacterial, fungal and viral infections. Objective: The objective of this study was to evaluate a possible relationship between oral shedding of human herpesviruses and xerostomia in patients with squamous cell carcinoma of head and neck submitted to radio/chemotherapy. Methods: In this study, oral rinse samples were collected weekly from 20 patients during radiotherapy. The samples were submitted to PCR and enzymatic digestion for detection of human herpesviruses. Xerostomia was evaluated according to the Seminars in Radiation Oncology criteria. Results: There was a higher frequency of grade 1 xerostomia (51.4%), observed first in the 1st week of radiotherapy. In the 4th week of radiotherapy, all patients presented some degree of xerostomia. Analysis of herpesviruses showed oral shedding of EBV, HHV-6 and HHV-7 in all weeks. Considering all the periods, the highest frequency was in patients with EBV excretion (55.0%), which was significantly higher than that of other viruses. Conclusion: We observed that oral shedding of herpesviruses was not affected by xerostomia as there was a progression in their excretion, even with the evolution of xerostomia. This suggested that there is a local replication in the oral cavity that is not completely dependent of salivary excretion.